Sustained Lipopolysaccharide-Induced Lung Inflammation in Mice Is Attenuated by Functional Deficiency of the Fas/Fas Ligand System - Matute-Bello, Gustavo (American Society for Microbiology, 2004)
To determine whether the Fas/Fas ligand (FasL) (CD95/CD178) system contributes to the development of an inflammatory response in vivo, 2.5 μg of bacterial lipopolysaccharide (LPS; endotoxin) per g was administered intranasally to healthy mice (C57BL/6) and mutant mice deficient in either Fas (lpr mice) or FasL (gld mice). Sustained LPS-induced neutrophilic inflammation in the lungs was attenuated in both lpr and gld mice. These observations provide further evidence of a proinflammatory role for the Fas/FasL system in the lungs.